2015
DOI: 10.1530/rep-15-0216
|View full text |Cite
|
Sign up to set email alerts
|

Role of macrophage secretions on rat polycystic ovary: its effect on apoptosis

Abstract: Polycystic ovarian syndrome is the most common endocrine disorder among women of reproductive age. Little is known about its etiology, although the evidence suggests an intrinsic ovarian abnormality in which endocrine, metabolic, neural and immune factors would be involved. In this work, the effects of macrophage (MO) secretion on ovarian apoptosis in a polycystic ovary syndrome rat model (PCO rat) induced by estradiol valerate are studied. Spleen MO secretions were used to stimulate ovaries and ovarian inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…These responses appeared to be follicle stage-specific and critical for normal follicle growth. DHT treatment disrupted the M1: M2 ratio and therefore the inflammatory versus anti-inflammatory signaling in the ovaries [34,35] and potentially contributing to the apoptosis in granulosa cells [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…These responses appeared to be follicle stage-specific and critical for normal follicle growth. DHT treatment disrupted the M1: M2 ratio and therefore the inflammatory versus anti-inflammatory signaling in the ovaries [34,35] and potentially contributing to the apoptosis in granulosa cells [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…2. In a previous study, we observed that MФ from PCO rats released more NO than Control MФ (Figueroa et al 2015). In this case, the SON section caused a decrease in the release of nitrites from PCO-SON MФ in relation to PCO MФ (P < 0.05).…”
Section: Effect Of Son Section On Tnfα and Nitrite Release From Pco Mmentioning
confidence: 59%
“…The measurement of serum A2 levels showed a decrease in PCO-SON rats compare to PCO rats, reaching a similar value to control rats (PCO: 1.88 ± 0.10; PCO-SON: 1.50 ± 0.12; C: 1.45 ± 0.07; ng/mL; PCO vs PCO-SON and C rats, P < 0.05). This, along with our previous results showing that the androgen microenvironment induces the production of TNFα by PCO MФ (Figueroa et al 2015), led us to determine whether the SON section affects TNFα release and its mRNA expression in PCO MФ. As shown in Fig.…”
Section: Effect Of Son Section On Tnfα and Nitrite Release From Pco Mmentioning
confidence: 73%
See 1 more Smart Citation
“…Cytokines secreted by splenic macrophages from PCOS mouse stimulated androstenedione production by granulosa cells and inhibited estradiol production, but the exact cytokines are unknown [ 66 ]. Excessive androgen inhibited the macrophage viability and increased macrophage apoptosis [ 67 ], and promoted pro-inflammatory cytokines expression, such as TNF-α [ 68 ]. The increased TNF-α in turn inhibited estradiol production [ 68 ].…”
Section: The Role Of Macrophages In Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 99%